Knowledge and practice among mothers of children with autism spectrum disorder on gluten free casein free diet in a tertiary medical centre of Bangladesh - Hasan, M. Mahmudul; Shefa, Jannatara; Akther, Jahanara; Korobi, Quaniz F. (International Journal of Research in Medical Sciences, 2025)
The gluten-free casein-free (GFCF) diet helps reduce hyperactivity and improve learning, cognitive function, and communication in children with autism spectrum disorder (ASD). Poor adherence and knowledge can lead to improper application, resulting in persistent health issues and hyperactive behavior. This study aimed to address these gaps. A descriptive cross-sectional study was conducted among 50 mothers of children with ASD on GFCF diet from August 2024 to January 2025 by purposive sampling technique. Descriptive statistics and Chi-square test were used to explore the knowledge and practices of the mothers and to identify factors affecting them using the statistical software. During the six-month study with a 100% response, 50 mothers of children with ASD (ages 18–35+) were interviewed. A significant association was found between mothers’ knowledge levels and GFCF diet practices (p<0.001). The study concludes that most mothers had medium knowledge and practice levels, highlighting the need for improved awareness to enhance dietary practices. Mothers’ moderate knowledge of the GFCF diet highlights the need for improved practices to address maladaptive behaviors. Future guidelines should consider enablers and barriers, as adherence remains incomplete (only GF or CF). A qualitative approach is recommended.